(untitled) (Journal of history, 2020)
This article is devoted to rebellion of 1916 in Kazakhstan, including national liberation movement of the Kazakh people in Semirechie as one of large hearts of rebellion, and also reflection of these events in poems of great poet Zambyl Zhabaev. A poet in the works presented the tight situ- ation of the Kazakh people, historical true of that time. Zhambyl actively participated in national liberation movement of 1916, was among the people acting against king’s decree, devoted the flaming invocatory songs to this movement. Poems of Zhambyl for us are precious treasure, very important historical source. Because, in the works he devoted to the events of 1916 certainly and thoroughly expounded a historical true. National lib- eration rebellion of 1916 is a basic theme in poems of Zhambyl Zhabaev